Constitution of Pornography in RI Number 44 in 2008 Perspective Maqashid Al-Syariah - Muh. Daming K. M.Ag, Dr; St. Halimang M.HI, Dr (International Journal of Engineering and Technology, 2018)
The main problems in this research, What the law Number 44 in 2008 about pornography by perspective Maqas}id al-Syari>ah. The topics were elaborated on three sub problem. (1) What the Content of The RI law about Pornography is. (2). What the weakness of pornography law is. (3) What pornography law from perspective Maqas}id al-Syari>ah is. This research is to understand substance of Law Number 44 in 2008. It would elaborate the weakness of this law and to elaborate that the content of pornography law is proper to Maqas}id al-Syari>ah. It would be used Syarâ€™i, Juridical, historical, and sociological approach. The result of research showed that the content of Pornography law consist of 8 chapters and 82 verses, they are general certainty, prohibition and limitation, children protection, prevention, investigation, providing guidance, interrogation in the court, annihilation, criminal certainty and closing certainty. The weakness of the law only arranges the pornography in the public by media, and it is not in private area. Specifically the pornography law did not arrange the action which can lead to the adultery prohibited by Islam. This research is hoped that legislative and government can invite Islamic law and do preventive action to the pornography.Â